Drying Shrinkage of Mortar Incorporating High Volume Oil Palm Biomass Waste - Abdul Shukor Lim, N.; Samadi, M.; Mohd Sam, A.; Abd Khalid, N.; Sarbini, N.; Ariffin, N.; Hussin, M.; Ismail, Mohamed (2018)
© The Authors, published by EDP Sciences, 2018. This paper studies the drying shrinkage of mortar incorporating oil palm biomass waste including Palm Oil Fuel Ash, Oil Palm Kernel Shell and Oil Palm Fibre. Nano size of palm oil fuel ash was used up to 80 % as cement replacement by weight. The ash has been treated to improve the physical and chemical properties of mortar. The mass ratio of sand to blended ashes was 3:1. The test was carried out using 25 × 25 × 160 mm prism for drying shrinkage tests and 70 × 70 ×70 mm for compressive strength test. The results show that the shrinkage value of biomass mortar is reduced by 31% compared with OPC mortar thus, showing better performance in restraining deformation of the mortar while the compressive strength increased by 24% compared with OPC mortar at later age. The study gives a better understanding of how the biomass waste affect on mortar compressive strength and drying shrinkage behaviour. Overall, the oil palm biomass waste can be used to produce a better performance mortar at later age in terms of compressive strength and drying shrinkage.